Full dimensional quantum-mechanical simulations for the vibronic dynamics of difluorobenzene radical cation isomers using the multilayer multiconfiguration time-dependent Hartree method - Meng, Qingyong; Faraji, Shirin; Meyer, Hans-Dieter (The journal of chemical physics, 2012)
Full dimensional multilayer multiconfiguration time-dependent Hartree (ML-MCTDH) calculations of the dynamics of the three difluorobenzene cationic isomers in five lowest-lying doublet electronic states using the ab initio multistate multimode vibronic coupling Hamiltonian (MMVCH) model are carried out using the Heidelberg MCTDH package. The same dynamical problems, but treated with the MCTDH scheme and using a reduced dimensional ab initio MMVCH model, have been previously reported [S. Faraji, H.-D. Meyer, and H. Köppel, “Multistate vibronic interactions in difluorobenzene radical cations. II Quantum dynamical simulations,” J. Chem. Phys. 129, 074311 (2008)]. For easy comparison with the reduced dimensional results, 11D or 10D ML-MCTDH calculations are also performed. Extensive ML-MCTDH test calculations are performed to find appropriate ML-MCTDH wavefunction structures (ML-trees), and the convergence of the ML-MCTDH calculations are carefully checked to ensure accurate results. Based on the appropriate ML-trees, the photoelectron (PE) spectrum and the mass analyzed threshold ionization (MATI) spectrum are simulated, analyzed, and compared with corresponding experimental spectra. Because of its efficient simulation capability for large systems, ML-MCTDH calculations save a considerable amount of central processing unit (CPU)-time, even when a reduced dimensional MMVCH is used, i.e., the same reduced model as in the corresponding MCTDH calculations. Simulations of the experimental PE spectra by full dimensional ML-MCTDH calculations reproduced main peaks, which originate from different electronic states. The agreement is improved as compared to the reduced dimensionality calculations. Unfortunately, the experimental PE spectra are not very well resolved. Therefore, we compare our calculations additionally with highly resolved MATI spectra, which, however, are only available for the ˜XX̃<mover accent="true">X̃</mover> state. Based on a series of ML-MCTDH simulations with longer propagation time for ˜XX̃<mover accent="true">X̃</mover>, a number of vibrational modes, including fundamentals, their combinations, and overtones are simulated and assigned by comparing with the experimental assignments and the ab initio frequencies. Excellent correlation between the experimental and full dimensional ML-MCTDH results show that ML-MCTDH is accurate and very efficient and that the ab initio MMVCH model is very suitable for ML-MCTDH calculations.